The Long Road to Changi - Ewer, Peter (Sydney : HarperCollins Publishers, 2013)
How flawed planning, dysfunctional personalities and empirical arrogance took Australia down the long road to Changi. In the 1930s while war raged in Europe, Australians were assured by politicians that the country was safe as long as the Union Jack fluttered over 'Fortress Singapore'. the reality was so different: Britain, over-stretched and under threat, skimped on the forces it needed to hold the base. When Japanese forces began flexing their muscles in the Pacific, a hasty defence plan was put in place. Australian troops, aircrews and sailors were dispatched to Singapore as much for purposes of propaganda as anything else. the understanding was that bronzed Aussies would soon put the Japs in their place. But it was so much wishful thinking. While most books centre on the horrors of the death camps, historian Peter Ewer asks how we came to be in this mess in the first place. Why was an untested Australian military contingent expected to play a leading role in halting the cream of the Japanese army? Why did British commanders and politicians send them there - then blame them for the inevitable defeat? Could this disaster have been averted? Drawing on fresh archival research, Ewer uncovers a story of incompetent planning, powerful but flawed characters and national trauma which resonates to this day. Writing from the perspectives of foot soldiers and generals, politicians and socialites, he constructs a riveting picture of a war which was lost before it began.
Imprint: ABC Books.
Description based on vendor-supplied metadata
Keywords: 1900 - 1999; Military history; World War, 1939-1945 -- Campaigns -- Singapore; World War, 1939-1945 -- Participation, Australian; World War, 1939-1945 -- Singapore; Armed Forces; History - General; History - General; Military campaigns; Military participation -- Australian; Second World War; Second World War; Australia -- Armed Forces -- Singapore -- History; Australia -- History, Military -- 20th century; Great Britain -- Armed Forces -- Singapore -- History; Singapore -- History -- Japanese occupation, 1942-1945.; Singapore -- History -- Siege, 1942.; Australia; Great Britain; Singapore; Australian; Electronic books; History